Perlindungan Hukum Bagi Pengguna Layanan Aplikasi Maxim dan Grabcar Sebagai Transportasi Berbasis Aplikasi Online - Asep Fernando (Jurnal Terekam Jejak, 2024)
Developments in the world of public transportation business are followed by legal protection as protection for users of public transportation services. With this legal protection, service users will always feel safe and comfortable when using public transportation services. Maxim and GrabCar have the status of limited liability companies (PT) which operate in the field of providing information technology-based (online) application services. These two companies facilitate the provision of public transport services in partnership with official public transport operating companies. This research explores the position and legal protection of Maxim and GrabCar in providing public transportation to users of the Maxim and GrabCar application services. The research uses qualitative methods. The research results show that it is hoped that the government will supervise the implementation of carriers' responsibilities to fulfill passengers' rights in public transport services.